THE BENEFITS OF STRENGTH TRAINING FOR CHILDREN AND ADOLESCENTS. (Fiep Bulletin - online, 2015)
The present research based on the bibliographical references will show the behavior of the some systems of the human body during the different phases of growth that, must be of extreme importance for the elaboration of a program of training for daily pay-pubescent and pubescent. In the training to strength can be stimulated some physical valences amongst these will go to destine itself to the present study, the force. Moreover, we will argue which is the cause of the increase of muscular force in children, in accordance with scientific studies. From this research we could perceive that the children are capable to get profits of force beyond waited for the growth the standard, to increase the bone development thus being able, to prevent injuries with the adequate training of force.
Keywords: growth; training of force; children.